The Influence Of Cash Holding And Taxes On Income Smoothing Moderated By Firm Value - Riki Sanjaya; Etty Murwaningsari (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
Companies will carry out various strategies in achieving profits, both operational strategies, financial strategies, and other strategies. The company's profit achievement will be seen through financial reports that are entirely transparent and under applicable regulations, namely the Standards of Financial Accounting (SAK) issued by the Institute of Indonesia Chartered Accountants (IAI). The research’ porpose is to test the influence of cash holding and tax on income smoothing, moderated by value of the entity. This research use data of the financial reports of Indonesia Stock Exchange with cyclical and non-cyclical sector companies in 2020-2022 period. As a research of causaltity, this study test the effect various variables independend to dependend. Method to analyze the variable, this research use a multiple regression with a purposive sampling technique. Based on the results showed that cash holding had no influence on income smoothing, while taxes had significant (positive) influence on income smoothing. In addition, entity value can not moderate the influence of cash holding and tax on income smoothing, also profitability (control variable) had significant (positive) influence on income smoothing.